Chile as Cultural and Political Benchmark for Anti-Franco Spain: Identification Mechanisms, Echoes and Parallels in Triunfo Magazine (1964-1980) - Sanz-Gavillon, Anne-Claire (Revista de Historia Social y de las Mentalidades, 2018)
The purpose of this article is to reflect on how political life in Chile was treated by the iconic Spanish magazine Triunfo between 1970 and 1979. We will start by taking a look at the articles about Chile in the publication between 1964 and 1980 and analysing them in a global manner. We will then focus on the change in tone surrounding the discussion of Chile in the magazine at the time, using a reverse-chronological format. Two main periods stand out for important changes in content and focus: the three years of the Allende government (1970–1973), in terms of how they were analysed in Francoist Spain, and the years 1973–1980, in which Chile sank further into the grip of dictatorship, while, in Spain, the Francoist era drew to a close.
Keywords: Chile; Spain; Allende's Goverment; Pinochet's Dictatorship; Antifranquist Press